2021
DOI: 10.1101/2021.05.07.443118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intergenerational adaptations to stress are evolutionarily conserved, stress-specific, and have deleterious trade-offs

Abstract: Despite reports of parental exposure to stress promoting physiological adaptations in progeny in diverse organisms, there remains considerable debate over the significance and evolutionary conservation of such multigenerational effects. Here, we investigate four independent models of intergenerational adaptations to stress in C. elegans (bacterial infection, eukaryotic infection, osmotic stress and nutrient stress) across multiple species. We found that all four intergenerational physiological adaptations are … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…2c). CYSL-1 and CYSL-2 are cysteine synthase-like proteins and have been implicated in hydrogen sulfide and cyanide detoxification 14,15,20,23,24 . While CYSL-2 can enzymatically convert cyanide to nontoxic β-cyanoalanine 14 , the essential role of CYSL-1 in cysl-2 p::GFP activation by amygdalin suggests CYSL-1 acts as a transcriptional regulator rather than a cysteine synthase or an enzyme to detoxify cyanide 15 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2c). CYSL-1 and CYSL-2 are cysteine synthase-like proteins and have been implicated in hydrogen sulfide and cyanide detoxification 14,15,20,23,24 . While CYSL-2 can enzymatically convert cyanide to nontoxic β-cyanoalanine 14 , the essential role of CYSL-1 in cysl-2 p::GFP activation by amygdalin suggests CYSL-1 acts as a transcriptional regulator rather than a cysteine synthase or an enzyme to detoxify cyanide 15 .…”
Section: Resultsmentioning
confidence: 99%
“…We treated cysl-2p::GFP animals with each of these amygdalin-derived molecules and found prunasin and cyanide (as in potassium cyanide) activated cysl-2p::GFP as amygdalin did, but others had no detectable effect (Figure 2C). CYSL-1 and CYSL-2 are cysteine synthase-like proteins and have been implicated in hydrogen sulfide and cyanide detoxification 16,17,22,24,25 . While CYSL-2 can enzymatically convert cyanide to nontoxic βcyanoalanine 16 , the essential role of CYSL-1 in cysl-2p::GFP activation by amygdalin suggests CYSL-1 acts as a transcriptional regulator rather than a cysteine synthase or an enzyme to detoxify cyanide 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the progeny of C. elegans submitted to various stressors demonstrate improvements in stress survival to the same and other types of stress. Recently, a study by Burton et al [7] examined multigenerational responses to a number of stressors including nutrient deprivation and pathogenic stress and found that multiple Caenorhabditis species regulate gene expression in the F1 generation in a stress-specific manner to benefit survival upon exposure to the same. These studies highlight the evolutionary advantage of provisioning offspring for what is perceived to be a likely future.…”
Section: Terminal Investment In Response To Cold May Have Evolved In Regularly Fluctuating Environmental Conditionsmentioning
confidence: 99%
“…The nematode Caenhorhabditis elegans recently arose as an ideal model for investigating stress-induced parental progeny investment. Several studies have detailed molecular tactics by which worms modify and provision gametes and embryos in response to dietary restriction, infection by pathogenic pseudomonads and microsporidia, and osmotic stress [4][5][6][7]. Among an array of environmentally-relevant stressors, though, the reproductive impacts of thermal stress (specifically cold stress) on C. elegans have not been closely assessed.…”
Section: Introductionmentioning
confidence: 99%